Micro hydro potential in West Malaysia - Raman N.; Hussein I.; Palanisamy K. (2023)
Combination of highland areas with huge river networks promise Malaysia with a lot of hydro power potential. To date Malaysia had utilized this potential in the range of large and mini hydropower but not in the micro hydro range. Micro hydro refers to power generation in the range of 5kW to 100kW. Micro hydro can provide alternative renewable energy sources especially in areas with small rivers or streams flowing. In identifying the micro hydro potential sites, reconnaissance studies is normally conducted. It is a preliminary study to identify micro hydropower potential. This paper presents the results of reconnaissance studies carried out to identify the micro hydro potential in West Malaysia. The reconnaissance studies were conducted with data from the Department of Survey and Mapping Malaysia, (JUPEM) and Metrological Department Malaysia. All the identified streams are located in areas which are accessible and/or showed evidence of settlements. Only streams with high head i.e. above 50m were considered in this study. From the reconnaissance studies, a total of 109 sites having micro hydro potential of about 20.4MW were identified. However, the energy demand for micro hydro was found not significant in West Malaysia as most areas are electrified. Still, micro hydro generation may serve as alternative renewable energy source in future amid rising electricity cost. 2009 IEEE.